Combined Effect of Midazolam and Bone Morphogenetic Protein-2 for Differentiation Induction from C2C12 Myoblast Cells to Osteoblasts - Yukihiko Hidaka; Risako Chiba-Ohkuma; Takeo Karakida; Kazuo Onuma; Ryuji Yamamoto; Keiko Fujii-Abe; Mari M. Saito; Yasuo Yamakoshi; Hiroshi Kawahara (Pharmaceutics, 2020)
In drug repositioning research, a new concept in drug discovery and new therapeutic opportunities have been identified for existing drugs. Midazolam (MDZ) is an anesthetic inducer used for general anesthesia. Here, we demonstrate the combined effects of bone morphogenetic protein-2 (BMP-2) and MDZ on osteogenic differentiation. An immortalized mouse myoblast cell line (C2C12 cell) was cultured in the combination of BMP-2 and MDZ (BMP-2+MDZ). The differentiation and signal transduction of C2C12 cells into osteoblasts were investigated at biological, immunohistochemical, and genetic cell levels. Mineralized nodules formed in C2C12 cells were characterized at the crystal engineering level. BMP-2+MDZ treatment decreased the myotube cell formation of C2C12 cells, and enhanced alkaline phosphatase activity and expression levels of osteoblastic differentiation marker genes. The precipitated nodules consisted of randomly oriented hydroxyapatite nanorods and nanoparticles. BMP-2+MDZ treatment reduced the immunostaining for both α1 and γ2 subunits antigens on the gamma-aminobutyric acid type A (GABAA) receptor in C2C12 cells, but enhanced that for BMP signal transducers. Our investigation showed that BMP-2+MDZ has a strong ability to induce the differentiation of C2C12 cells into osteoblasts and has the potential for drug repositioning in bone regeneration.